Reconsidering Legal Protection: The Urgent Need to Regulate the Retirement Age of Worker - Indra Pambudi Raharjo; Syofyan Hadi (Magister Ilmu Hukum Fakultas Hukum Universitas 17 Agustus 1945 Surabaya, 2026)
The absence of a national legal norm that explicitly regulates the retirement age of workers in Indonesia has created a normative vacuum that generates legal uncertainty, enables arbitrary practices in employment relations, and increases the potential for industrial relations disputes. This study aims to analyze how the state should exercise its role in providing legal protection for workers and to explain the urgency of regulating the retirement age within the framework of Indonesian labor law. The research employs a normative legal method using statutory, conceptual, and comparative approaches, including an examination of retirement-age regulation in selected ASEAN countries such as Malaysia, Thailand, and the Philippines. The findings show that workers constitute a vulnerable group requiring state protection, and that the normative vacuum regarding retirement age has resulted in inconsistencies and discriminatory practices in company-level retirement policies. The divergence between the retirement age set by companies and the requirements of the Pension Benefit Program under Government Regulation No. 45 of 2015 further contributes to legal uncertainty concerning workers’ rights to pension benefits. Comparative analysis demonstrates that several ASEAN countries have adopted clear, uniform retirement-age standards as instruments of legal and social protection. The novelty of this study lies in its normative argument that the Indonesian state, as a Pancasila-based rule-of-law state, must establish a clear, firm, and legally certain national retirement-age standard as a form of preventive legal protection and as a mechanism to ensure workers’ welfare in old age.